The Use of Drilling Techniques Integrated with Technology to Improve Students’ Vocabulary Mastery - Dwimayoga, I Made; Dewi, Kadek Sintya; Mahendrayana, Gede (English Education Department STKIP Agama Hindu Singaraja, 2024)
The purpose of this study is to improve vocabulary mastery through the use of drilling techniques integrated with technology. This study is classroom action research. 21 4th grade students of SDN 1 Tunjung were the subjects of this study. The necessary data were collected through vocabulary tests and direct interviews with students. The results showed an increase in the average score of students from the pretest of 39.76, increased in the post-test 1 to 72.14, and ended in post-test 2 with a score of 88.33. In addition, the positive response from students regarding the application of drilling techniques integrated with technology supports the statement that drilling techniques integrated with technology are the appropriate solution in improving English vocabulary mastery, especially at the elementary level.